(untitled) (Research, Society and Development, 2020)
Forensic Odontology is the science that correlates dental and legal principles, used for processes such as human identification. One of the possible acting fields for Forensic Odontologists is the analysis and study of patterns and injuries created by human bite marks. This study aimed to show the applicability of dental marks printed in chewing gum for human identification in forensic investigations. A transversal observational study was carried out. The data was collected from 20 volunteers over 18 years old. Each subject had their upper and lower dental casts and was asked to chew a piece of gum for one minute. The pieces of chewing gum were refrigerated at -20ºC for a week, and reproduced with addition and condensation silicones using an adapted reproduction technique. The analysis of the chewing gum was made by overlays. The ANOVA test showed no significant differences on width and length between the pieces of chewing gum and their reproductions (greatest width p=0.918, and the length p=0.981). The analysis of the reproductions with plaster mold showed that there was no difference when using addition silicone or condensation silicone. During the analysis, various suspects could be excluded from the investigation (up to 11, depending on the technique used), but it was not possible to confirm one of them as the main suspect. The study showed that the reproduction technique of chewing gum is efficient, viable and easily performed; and can be used in cases of human identification in forensic investigations. However, it is necessary to certify that the chewing gum effectively presents a bite mark and that it is correctly handled to avoid alterations. It also became evident that the process of refrigeration is essential for the analysis proposed in this study.